2020
DOI: 10.14309/ajg.0000000000000682
|View full text |Cite
|
Sign up to set email alerts
|

Opioids Interfere With Deglutitive Inhibition Assessed by Response to Multiple Rapid Swallows During High-Resolution Esophageal Manometry

Abstract: INTRODUCTION: Normal response to multiple rapid swallows (MRS) during high-resolution esophageal manometry is deglutitive inhibition; opioids may interfere with this. The aim of this study was to evaluate the response to MRS in patients on opioids, not on opioids, and healthy controls. METHODS: Response to MRS was evaluated for complete vs impaired inhibition in 72 chronic opioid users, 100 patients not on opioids, and 24 healthy controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 11 publications
6
32
0
Order By: Relevance
“…This excitatory-inhibitory "imbalance" would induce spastic motor disorders of distal esophagus including the reduced latency as seen in DES and impaired LES relaxation seen in EGJOO. 26,27 The current findings illustrate the inhibitory effect of codeine on esophageal primary peristalsis, which is similar to that reported in previous studies. 15,23,[26][27][28] Figure 1 Effects of codeine on 4-s integrated relaxation pressure (IRP-4s) of primary esophageal peristalsis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This excitatory-inhibitory "imbalance" would induce spastic motor disorders of distal esophagus including the reduced latency as seen in DES and impaired LES relaxation seen in EGJOO. 26,27 The current findings illustrate the inhibitory effect of codeine on esophageal primary peristalsis, which is similar to that reported in previous studies. 15,23,[26][27][28] Figure 1 Effects of codeine on 4-s integrated relaxation pressure (IRP-4s) of primary esophageal peristalsis.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies utilizing HRM have shown that opioids use increased LES pressure and is associated with hypercontractility. 15,23,[26][27][28] A large sample size series conducted by Ratuapli et al 15 further demonstrated an association between chronic opioid use and esophageal motor dysfunction. They found that the main opioid-related esophageal disorders are EGJOO and type III achalasia, and the other dysmotility described are distal esophageal spasm (DES) and hypercontractile esophagus, a clinical entity which has been termed opioid-induced esophageal dysfunction (OIED).…”
Section: Discussionmentioning
confidence: 98%
“…10 More recently, the same research group reported that chronic opioid use affects deglutitive inhibition of the esophageal body during the multiple rapid swallows (MRS), a provocative maneuver during HRM. 11 Furthermore, little is known about the effects of opioids in the proximal region of the esophagus, the upper esophageal sphincter (UES), and the pharynx. Smiley et al noted in a case study a decreased or absent swallowing function and gag reflex as a rare, but repetitive symptom after administration of the opioid fentanyl in healthy pregnant women during labor.…”
Section: Introductionmentioning
confidence: 99%
“…Median values (interquartile range) for esophageal pressure flow analysis neural pathways which results in abnormal contractile activity during MRS 11. Additionally, this study was the first to unravel the effect of a non-prescription opioid on the esophagus using PFA, which combines contractile activity and bolus flow.…”
mentioning
confidence: 97%
“…There is limited data to explain the pathophysiologic mechanisms of OIED, but the proposed mechanism is that chronic opioids interfere with inhibitory neural signaling leading to unregulated excitatory control in the esophagus. 6-9…”
Section: Opioid-induced Esophageal Dysfunction (Oied)mentioning
confidence: 99%